LEGAL PROTECTION OF PERSONAL DATA AS PRIVACY RIGHTS OF E-COMMERCE CONSUMERS AMID THE COVID-19 PANDEMIC - Raphael Haganta, (Universitas Negeri Semarang, 2020)
The use of e-commerce in the midst of the COVID-19 pandemic shows an increase. This is due to publication of several regulations that limit everyone's activities outside the home, affecting conventional trading activities online by utilizing e-commerce. Although providing benefits during the pandemic, e-commerce has a vulnerability to personal data protection. Through this paper, the authors use normative legal research methods, intending to know the concept of personal data as a right of privacy and the construction of Indonesia's positive law in legal protection of the personal data of e-commerce consumers.